Co-designing with the archive: a new way of interacting with fashion design heritage - Nicola Besana; Marianne Graves Petersen; Peter Gall Krogh; Davide Spallazzo (European Journal of Cultural Management and Policy)
The rise of digitally interactive archives has introduced new opportunities for more proactive interactions with historical fashion collections. This paper explores how contemporary fashion archives are evolving, focusing on their current framework of interaction and how these could be further enhanced through the integration of advanced digital technologies, such as extended reality (XR), which includes virtual (VR) and augmented reality (AR), and artificial intelligence (AI), considering machine learning (ML) as well. Given the structured, heterogeneous and richly labeled nature of fashion archives - garments images, dates, labelled details, digital twins and inspirational material - they are particularly well-suited for integrating emerging technologies, such as XR and AI systems, and for exploring new roles in the user-archive interaction. This possible shift has been investigated through the analysis of a workshop, where fashion and interaction design students explored how interactive technologies can serve as a vehicle for novel ways of engaging with the fashion cultural heritage of a given fashion designer, leading to highlighting the potential for a more proactive role of archives in fashion design. The findings lead us to propose a possible new framework where fashion interactive archives act not only as repositories but as proactive co-creators, enabling a more dynamic dialogue between the user and the archive.